2017
DOI: 10.1186/s13256-017-1437-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pruritus in a palliative care patient with low-dose paroxetine: a case report

Abstract: BackgroundPruritus is a distressing symptom seen in palliative care. There is limited high-quality evidence of pharmaceutical treatments for pruritus in palliative care, including the use of paroxetine.Case presentationI present a case of a 70-year-old caucasian woman with metastatic ovarian cancer who presented with severe pruritus. She had been diagnosed with bile duct obstruction 1 month earlier. Antihistamines and over-the-counter skin creams were first trialed, to no effect. Paroxetine was started at 5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Thus, the prospect of using paroxetine based GRK2 inhibitors against allergic asthma is an attractive possibility. Furthermore, a randomized control trial also revealed that paroxetine has been successful for therapy against pruritus ( 39 , 40 ), which is likely mediated via MC activation. Thus, in such precedent where paroxetine is clinically approved, paroxetine-based inhibitors may be attractive therapeutics against allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the prospect of using paroxetine based GRK2 inhibitors against allergic asthma is an attractive possibility. Furthermore, a randomized control trial also revealed that paroxetine has been successful for therapy against pruritus ( 39 , 40 ), which is likely mediated via MC activation. Thus, in such precedent where paroxetine is clinically approved, paroxetine-based inhibitors may be attractive therapeutics against allergy.…”
Section: Discussionmentioning
confidence: 99%